Le retour du gnosticisme - E. Kayayan (Acta Theologica)
Gnosticism, the last religion to have arisen during Western Antiquity, has its roots both in Greek thought and in late Judaism. The links between antique Gnosticism and modern offsprings such as the New Age movement have often been singled out the last fourty years. However, their common ontological features have not yet been adequately put into evidence. This article explores some of these features, in particular the way in which both forms of Gnosticism relate to Christianity: borrowing some of its teachings they forge a belief system in which an ontological continuity between God and mankind is asserted, while the relation between the one and the many becomes blurred.